Multifaceted Treatment and Therapies in the Care of Children with Cerebral Palsy – A Literature Review - Wilewska, Anna; Pomirski, Bartosz; Pomirska, Agata; Biernikiewicz, Julia; Biernikiewicz, Milena; Alabrudziński, Konstanty; Borowiec, Agnieszka; Borowiec, Kinga; Kwaśniewska, Paulina; Graczyk, Patryk (Journal of Education, Health and Sport, 2024)
Introduction and Purpose: Cerebral palsy (CP) is a prevalent neurological disorder in children, characterized by movement, muscle tone, and posture impairments. This article reviews the clinical and therapeutic management of CP, focusing on spasticity, musculoskeletal disorders, and holistic rehabilitation. It examines evidence-based interventions, including onabotulinumtoxinA, intrathecal baclofen pumps, and surgical options for orthopedic deformities. Key rehabilitation techniques such as neurodevelopmental therapies, gait training, and speech therapy are discussed to enhance motor skills and cognitive development. Additionally, the management of associated conditions like epilepsy and intellectual challenges is addressed, emphasizing psychological support for patients and families. The purpose of this article is to provide a comprehensive overview of the current state of knowledge regarding the management of cerebral palsy. Material and Methods: We utilized English databases such as PubMed, Google Scholar, Cochrane, and PubMed Central, selecting articles based on keywords like cerebral palsy, spasticity, physical therapy, and rehabilitation. State of Knowledge: Effective CP management requires a multidisciplinary approach to tackle motor impairments, spasticity, deformities, and psychosocial challenges. Therapeutic interventions, including pharmacological treatments, surgical options, and innovative rehabilitation techniques, are essential for improving mobility and quality of life. Summary: Comprehensive care for children with CP is crucial. Evidence supports combining multiple therapeutic approaches tailored to each child’s needs and involving family preferences to optimize development and well-being.